Behavioral impairment and cognition in Thai adolescents affected by HIV. (9th February 2021) - Patel, Payal B.; Belden, Andrew; Handoko, Ryan; Puthanakit, Thanyawee; Kerr, Stephen; Kosalaraksa, Pope; Ounchanum, Pradthana; Kanjanavanit, Suparat; Aurpibul, Linda; Ngampiyasakul, Chaiwat; Luesomboon, Wicharn; Mellins, Claude A.; et al.
Abstract: Background: Cognitive and behavioral impairment are common in children living with perinatally acquired HIV (pHIV) and children exposed to HIV in utero but uninfected (HEU). Methods: We sought to determine the prevalence of adverse behavioral symptomatology using a Thai-translated and validated version of the SNAP-IV questionnaire and assess cognitive function utilizing the Children's Color Trails Test, Delis-Kaplan Executive Function System, and the Wechsler Intelligence Scales, in our cohort of Thai adolescents (10–20 years old) with well-controlled pHIV compared to HEU and HIV-unexposed, uninfected youth. We then evaluated the interaction between HIV status, behavioral impairment, and executive function outcomes independent of demographic variables. Results: After controlling for demographic factors of age and household income, adolescents with pHIV had higher inattentive symptomatology and poorer neuropsychological test scores compared to uninfected controls. Significant interactions were found between inattention and executive function across multiple neurocognitive tests. Conclusions: Behavioral impairment and poor executive functioning are present in adolescents with well-controlled pHIV compared to HIV-uninfected matched peers. The SNAP-IV questionnaire may be a useful tool to identify those with attentional impairment who may benefit from further cognitive testing in resource-limited settings.